Modular Organization of Brain Resting State Networks in Chronic Back Pain Patients - Balenzuela, Pablo; Chernomoretz, Ariel; Fraiman, Daniel; Cifre, Ignacio; Sitges, Carolina; Montoya, Pedro; Chialvo, Dante R. (Frontiers in Neuroinformatics, 2010)
Recent work on functional magnetic resonance imaging (fMRI) large scale brain networks under resting conditions demonstrated its potential to evaluate the integrity of brain function under normal and pathological conditions. A similar approach is used in this work to study a group of chronic back pain patients (CBP) and healthy controls (HC) to determine the impact of long enduring pain over brain dynamics. Correlation networks were constructed from the mutual partial correlations of brain activity's time series selected from ninety regions using a well validated brain parcellation atlas. The study of the resulting networks revealed an organization of up to six communities with similar modularity in both groups, but with important differences in the membership of key communities of frontal and temporal regions. The bulk of these findings were confirmed by a surprisingly naive analysis based on the pairwise correlations of the strongest and weakest correlated healthy regions. Beside confirming the brain effects of long enduring pain, these results provide a framework to study the effect of other chronic conditions over cortical function.